Best plays of Racine - Racine, Jean, 1639-1699 (Princeton legacy library., 2017)
Racine's masterpieces--Andromaque, Britannicus, Phedre, and Athalie--are translated into English verse. The introduction and notes by Mr. Lockert guide the reader to a greater understanding of the plays. Originally published in 1966. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.